Bio-Technological Characterization of the Saccharomyces bayanus Yeast Strains in Order to Preserve the Local Specificity - Enikő Gaspar; Letiția Oprean; Ecaterina Lengyel; Ramona Iancu; Horia Oltosutean (Scientific Papers Animal Science and Biotechnologies, 2023)
The wine yeasts have multiple and important applications in the industry, aiming to obtain pure cultures and the selection of those strains which, according to the lab investigations, present superior bio-technological properties.